Mind Mapping in Teaching Writing - Mukmin Mukmin; Handrini Afriyanti (English Education Study Program, 2020)
The objective of this research is to know whether the students’ ability in writing descriptive text using mind mapping in Madrasah Aliyah Negeri 1 Banggai can improve or not and to know how mind mapping improve the students’ ability of writing. This research was quasi experimental research by using non-equivalent design. The population of this research were all of the tenth grade students’ in Madrasah Aliyah Negeri 1 Banggai. The sample were X science 1 and X science 2 and consist of 35 and 34 students. The instrument of this research was written test. The kinds of test were pre-test and post-test. The mean of pre-test score in experimental class is 41 and the mean of post-test in experimental class is 83. The mean of pre-test score in controlled class is 37.35 and the mean of post-test in controlled class is 47.65. From the calculation of tcounted was higher than ttable, the result of tcounted is 18.80 meanwhile ttable in the degree of significance 0.05 is 1.66792. If the tcounted> ttable, it means that Ha is accepted. It shows that the comparison of tcounted and ttable is 18.80 > 1.66792. In the other words the alternative hypothesis is proven. It assumed that mind mapping technique can improve the students’ ability of writing descriptive text.Keywords: Writing Ability; Descriptive Text; Mind Mapping.